Pertukaran Sosial Di Kalangan Penghobi Modifikasi Motor Di Jakarta Selatan - Soeoed, Athallah Bentang Lazuardi (Socio-political Communication and Policy Review, 2025)
This study examines the dimensions of social exchange among motorcycle modification enthusiasts in South Jakarta. The phenomenon of increasing motorcycle modification activities among young people is not only oriented towards aesthetics and function but also builds strong social interactions between community members. The purpose of this study is to understand the process and form of social exchange and the role of the community in building the social identity of motorcycle hobbyists. The method used is a qualitative approach with participatory observation techniques and in-depth interviews, resulting in a deep understanding of the social dynamics of the community. The results of the study show that motorcycle modification enthusiasts carry out social exchanges in the form of sharing knowledge, experiences, resources (such as spare parts and funds), and appreciation for the work and participation of members. The community becomes a place to strengthen friendship, identity, and social status. Social exchange in this community plays an important role in modification activities, as well as strengthening social and socio-cultural ties among urban youth. This study provides an overview that motorcycle modification hobbies are not just individual activities, but also a form of constructive and positive social interaction. Abstrak Penelitian ini mengkaji dimensi pertukaran sosial di kalangan penghobi modifikasi motor di Jakarta Selatan. Fenomena meningkatnya kegiatan modifikasi motor di kalangan muda yang tidak hanya berorientasi pada estetika dan fungsi tetapi juga membangun interaksi sosial yang kuat antar anggota komunitas. Tujuan penelitian ini adalah untuk memahami proses dan bentuk pertukaran sosial serta peran komunitas dalam membangun identitas sosial penghobi motor. Metode yang digunakan adalah pendekatan kualitatif dengan teknik observasi partisipatif dan wawancara mendalam, sehingga menghasilkan pemahaman mendalam tentang dinamika sosial komunitas. Hasil penelitian menunjukkan bahwa penghobi modifikasi motor melakukan pertukaran sosial berupa berbagi pengetahuan, pengalaman, sumber daya (seperti sparepart dan dana), serta penghargaan atas karya dan partisipasi anggota. Komunitas menjadi wadah untuk memperkuat rasa persahabatan, identitas, dan status sosial. Pertukaran sosial di komunitas ini memainkan peranan penting dalam kegiatan modifikasi, sekaligus memperkuat ikatan sosial dan sosial budaya di kalangan muda perkotaan. Penelitian ini memberikan gambaran bahwa hobi modifikasi motor tidak hanya sekadar kegiatan individual, melainkan sebagai bentuk interaksi sosial yang konstruktif dan positif.